PENGARUH TRANSFER PRICING, CAPITAL INTENSITY DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Nova Gradisca Wirantika; Nurhayati (Jurnal Nusa Akuntansi, 2026)
This research aims to analyze the effect of transfer pricing, capital intensity, sales growth on tax avoidance. This research was conducted by analyzing the financial statements of companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The sample used in this research was 10 consumer non-cyclical sector companies on the Indonesia Stock Exchange during the period 2019 to 2023 using the purposive sampling technique. The data used in this research are secondary data in the form of financial statements from each company that has been used as a research sample. The variables used in this research are Transfer Pricing as the first independent variable, Capital Intensity as the second independent variable, and Sales Growth as the third independent variable and Tax Avoidance as the dependent variable. The panel data regression method is used as the research methodology in this study. The analysis of the research results uses the help of EViews 13 Student Version Lite software. The results of the study show that the best model is the Fixed Effect Model (FEM). The results of this study indicate that Transfer Pricing partially affects Tax Avoidance, Capital Intensity partially affects Tax Avoidance, Sales Growth partially does not affect Tax Avoidance, and simultaneously Company Size, Capital Intensity, Sales Growth affect Tax Avoidance.